Metaphors in political tweets during national elections - Ramanathan, Renugah; Tan, Bee Hoon; Paramasivam, Shamala (Universiti Putra Malaysia Press, 2018)
The use of metaphors in political discourse has been constantly researched through the decades. Primarily, metaphors act as a rhetorical device in political discourse aimed at characterising political figures, opponents, events and citizens in persuading them towards a specific point of view. This study discovers the various types of conceptual metaphors employed in the tweets of the Malaysian Prime Minister Dato' Seri Najib Razak (henceforth, Najib) and the Indian Prime Minister Narendra Modi (henceforth, Modi) throughout their election campaign in their respective countries. The Metaphor Identification Procedure (MIP) as proposed by Pragglejazz Group has been adopted for examining the election tweets in-depth and to indicate possible metaphorical linguistic expressions (MLEs). Furthermore, the cognitive metaphor framework by Lakoff and Johnson has been employed in analysing the emerging conceptual metaphorical themes in the tweets of both the political premiers. Results from the analysis have portrayed fascinating underlying conceptual metaphors and metaphorical linguistic expressions in the tweets of both the political figures. The findings revealed that the use of conceptual metaphors in the political tweets induces specific understanding of how political activities throughout the election are conceptualised and expressed in denoting particular ideological stances.